Regulation of The Provision of Covid-19 Vaccination in Indonesia as The Implementation of State Obligations in line with The Indonesian Constitution - Mery, Lisa; Rahmah, Andi; Wulandari, Andi Sry Rezki (Faculty of Law, Universitas Pattimura, 2021)
This study aims to provide a clear picture of the steps (efforts) of the government of the Republic of Indonesia to provide vaccines to its people evenly and free of charge according to the standards or procedures in the Health Law which is a derivative of the constitutional mandate of the Republic of Indonesia, the research method uses normative juridical research that combines the rule of law. With law enforcement which is a regulation of the Indonesian government, the results of the study provide a perspective that various ways have been attempted by the Indonesian government to overcome the Covid-19 virus pandemic, vaccines are a continuous hope to increase immunity and immunity of community groups which will certainly have a positive impact with the release of the Indonesian state from health threats and a spike in the increase in cases during the global pandemic. The conclusion of this study is that the Indonesian government has made intensive and accurate efforts to protect citizens and build group immunity which of course has an impact on the positive possibility that the Indonesian state and nation can get out of worries due to the Covid-19 pandemic.